Situating Portfolios - Yancey, Kathleen (University Press of Colorado, 1997)
Yancey and Weiser bring together thirty-one writing teachers from diverse levels of instruction, institutional settings, and regions to create a stimulating volume on the current practice in portfolio writing assessment. Contributors reflect on the explosion in portfolio practice over the last decade, why it happened, what comes next; discuss portfolios in hypertext, the web, and other electronic spaces; and consider emerging trends and issues that are involving portfolios in teacher assessment, faculty development, and graduate student experience. Contributors include Peter Elbow and Pat Belanoff, Gail Hawisher and Cynthia Selfe, Brian Huot, Sandra Murphy, and William Condon.